Sig y análisis espacial en la arqueología de cazadores recolectores de Magallania (extremo sur de Sudamérica) - Pallo, Mariá Cecilia, (Access archaeology., 2017)
Magallania defines the region between the Santa Cruz river basin to the north and the Fuegian expression of the Andes to the south. It is one of the southernmost spaces in the world and the last to be occupied by humans, a process that occurred at least at the end of the Pleistocene (11,000 to 9,000 AP) and before the complete formation of the Strait of Magellan (ca. 8000 AP). Thereafter, the Strait functioned as a biogeographic barrier, creating conditions for divergent cultural evolution between the populations of the mainland and Tierra del Fuego. For this reason, the archeology of Magallania offers a unique possibility to inquire about the relationship between the environmental dynamics and the spatial organization of populations of hunter-gatherers settled on both sides of the Strait of Magellan.